The Role of the Catholic Church in Overcoming Community Poverty Around the Area of St. Bonifasius Chapel Landungsari Malang - Triaditama, Setyawan; Sarmini, Sarmini; Jacky, M; Harianto, Sugeng; Mufid, Muhammad Khoirul Annas Waladul (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
The Catholic Church is actively involved in efforts to overcome the problems that exist in the world manifested by Catholics in the involvement of the weak, poor, and suffering. This study aims to analyze the role of the Catholic Church in overcoming poverty in the community around the area of St. Bonifasius Chapel Landungsari Malang. This study uses a qualitative approach with a descriptive type and case study design. The location of the research was carried out around St. Bonifasius Chapel Landungsari Malang. The data collection technique in this study uses observation and interviews. The data analysis technique used is Miles and Huberman’s data analysis technique which consists of four stages, namely data collection, data reduction, data presentation and conclusion or verification. The results of the study show that the majority of people around St. Bonifasius Chapel Landungsari Malang are daily workers whose income is unstable. Some also become city transportation drivers, but do not own their own cars so they have to pay rent. This poverty is caused by low income and lack of education. The Catholic Church plays a role in overcoming poverty with love, the tri-duty of the church, and practicing the Church’s Social Teachings. One example of the role of the Catholic Church is to provide jobs, educational assistance, and basic necessities to the surrounding community. The Church also conducts free health checkups.